Filling the gap between evidence, policy and practice: are 45 and Up Study researchers planning for impact? - Tam C Ha; Martin McNamara; Luciano Melo; Emma K Frost; Gabriel M Moore (Sax Institute, 2023)
Aim: To improve health outcomes, policy and practice decisions should be guided by relevant and timely evidence. High-quality, large-scale population data could play an essential role in supporting evidence-based decision making. The 45 and Up Study is a long-term, large-scale cohort study with more 250 000 participants aged 45 years and over from New South Wales (NSW), Australia. Data collected by the Study is accessible to researchers, government and non-governmental bodies. The study aimed to identify the proportion of researchers using data from the Study who intended to have an impact and achieved impact; the types of impact they intended and achieved; and the pathways through which they achieved it. Methods: Using data extracted from the application, progress and final report documents for 25 projects using 45 and Up Study data from January 2011 until December 2017, we a) determined the proportion of projects that intended to have policy or practice impact and b) described the type of policy and practice impact achieved. Results: We found that 88% (n = 22) of projects intended to have a policy or practice impact. Of those, 68% (n = 15) planned to influence or inform a policy or program, and 41% (n = 9) planned to share findings at conferences or in journals. Almost half of projects with intended impact (45%, n = 10) did not state how they planned to achieve impact. Approximately 16% of all projects (n = 4) reported achieving an impact on policy or services. The type of impact achieved by all four of these projects was influencing, informing or changing a policy or program. One of these four projects also achieved a change to legislation or regulation. Conclusions: Further strategies to promote a targeted approach to impact planning in research projects using datasets such as the 45 and Up Study would help guide researchers in achieving impact.